Optimalisasi Jaringan Air Bersih Kota Merauke - Biatma Syanjayanta; Anton Topan; Hilarius Candra Syanjayakusuma (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
Clean water services plan in Merauke district have not been running optimally. The lack of management, service and maintenance from the government affects the condition of the utility of the city of Merauke. The not yet optimally creating the utility of the city of Merauke is also one of the main problems of the clean water source network system. During the dry season, there is often difficulty in getting clean water. This study evaluates the existing conditions, then analyzes and makes the planning of clean water networks aimed at improving the conditions and quality of water supply services for residents of Merauke city. The results of this study are (1) Clean water plan, has not been evenly distributed and has not carried out maximum care. (2) The need for additional clean water distribution channels, maintenance of clean water pipelines and the need for filtration so that clean water is suitable for drinking. (3) It is necessary to add locations of raw water sources, water treatment plans, reservoirs and piping plan (see figure 13) to all urban settlements, so that optimal service equity can occur.